PENGARUH KEJELASAN SASARAN ANGGARAN, PENGENDALIAN AKUNTANSI, SISTEM PELAPORAN TERHADAP AKUNTABILITAS KINERJA SKPD DI MERAUKE - Hidayattullah,, Afilu; Herdjiono, Irine (Proceeding SENDI_U, 2015)
The research aimed to analyze the effect of budget goal clarity, controls accounting and systems reporting forperformance accountability of toward government agencies. respondents in this research is the civil servants whoserved as head of finance , program and evaluation , treasurer and finance staff in 27 SKPD of District Merauke.The amount of samples in this study was 116 respondents. The sample collection method using a basic formulaYamane, while the method of processing data using multiple linear regression analysis. The partial testing resultsshowed that the goal budget clarity, accounting controls and reporting systems have significant effect onperformance accountability of government agencies and simultaneous testing showed significant positive effect onperformance accountability of government agencies in Merauke.Key-Words: budget, accountability, performance, control, system